The Effects of Oxidative Stress in Urinary Tract Infection - Ergul Belge Kurutas; Pınar Ciragil; Mustafa Gul; Metin Kilinc (Mediators of Inflammation)
We aimed to determine the effects of oxidative stress in urinary tract infection (UTI). One hundred sixty-four urine samples obtained from patients with the prediagnosis of acute UTI admitted to the Faculty of Medicine, Kahramanmaras Sutcu Imam University, were included in this study. Urine cultures were performed according to standard techniques. Urinary isolates were identified by using API ID 32E. The catalase and superoxide dismutase activity and the lipid peroxidation levels known as oxidative stress markers were measured in all urine samples. Thirty-six pathogen microorganisms were identified in positive urine cultures. These microorganisms were as follows: 23 (63.8%) E coli, 5 (13.8%) P mirabilis, 4 (11.1%) K pneumoniae, 2 (5.5%) Candida spp, 1 (2.7%) S saprophyticus, and 1 (2.7%) P aeruginosa. It was observed that lipid peroxidation levels were increased while catalase and superoxide dismutase activities were decreased in positive urine cultures, compared to negative cultures. We conclude that urinary tract infection causes oxidative stress, increases lipid peroxidation level, and leads to insufficiency of antioxidant enzymes.